Embedded LES of thermal stratification effects on the airflow and concentration fields around an isolated high-rise building: Spectral and POD analyses. (December 2021) - Masoumi-Verki, Shahin; Gholamalipour, Payam; Haghighat, Fariborz; Eicker, Ursula
Abstract: Non-isothermal stratification conditions can alter the airflow pattern and pollutant dispersion process within urban areas. The present study is focused on the impact of various stratification conditions, namely, stable, isothermal (neutral), and unstable, on the airflow and concentration fields around an isolated high-rise building. Zonal Reynolds-averaged Navier-Stokes (RANS)-large eddy simulation (LES), also known as embedded large eddy simulation (ELES), is employed for simulating the airflow and concentration fields under non-isothermal boundary layers in order to make a balance between computational costs and accuracy. Comparing the results predicted by the present ELES with an available LES study, with almost similar computational settings (i.e., the inflow turbulence generation method, grid resolution, etc.) shows better performance of ELES in predicting the concentration field. The findings also illustrate that the impact of the unstable stratification condition on turbulence statistics is more pronounced than that of the stable stratification condition. The present article also investigates the effect of thermal stratification conditions on the mechanisms of pollutant dispersion, namely, convective and turbulent diffusion fluxes. The findings reveal that an increase in turbulence kinetic energy (TKE), caused by the unstable thermal stratification condition, increases the concentration fluctuations, which causes the pollutant concentration to be decreased. Furthermore, spectral and proper orthogonal decomposition (POD) analyses are performed for all stratification scenarios. The results show that by altering the thermal condition from isothermal to non-isothermal, either stable or unstable conditions, the contribution of the primary dominant modes to total TKE increases. Highlights: Embedded LES (ELES) is used to model dispersion under various stratification conditions. Impact of thermal stratification conditions on turbulence statistics is analyzed. Impact of thermal stratification conditions on pollutant dispersion mechanisms are analyzed. Spectral and POD analyses of flow field are performed under various stratification conditions.